Sustaninable arctic marine tourism development:Scale and scope for communnity investment, coordination, and action - Horbel, Chris; Kaiser, Brooks Alexandra; Menezes, Dwayne Ryan (Springer, 2022)
An interdisciplinary and inter-sectoral group of academics, tourism practitioners, community and governmental representatives have met and traveled together for workshops on Sustainable Arctic Tourism Development in Finnmark, Norway (April, 2018) and northern Iceland (March, 2019). This chapter describes and analyzes lessons from these workshops on the interdependent roles of local community action and government intervention in sustainable tourism development. Tourism is envisioned to provide opportunities to sustainable economic development in the Nordic Arctic. However, community concerns range widely, including from lack of tourists in some areas to overtourism in others. More concretely, they include concerns about how to conserve and share resources such as fishery stocks or marine mammal populations across growing, and uncertain, multi-use demands. The scale and scope of community action across a variety of forms, including local entrepreneurship and investment, the formation of resource conservation associations and/or associations that increase local tourism capacities as well as balance of power in negotiations with larger-scale tourism activities (e.g. large cruise ships), shapes the scope and need for government interventions, including direct and indirect regulations (e.g. access limits vs. sanctions for unfair business practices such as price gouging), monitoring, investments, and related decision-making. Community engagement and government action co-evolve; both positive and negative feedback loops are possible, and the cases experienced through the workshop highlight ways to promote successful, self-reinforcing community outcomes and avoid negative ones.